Isoforms of Melanopsin Mediate Different Behavioral Responses to Light - Jagannath, Aarti (Curr Biol, 2015)
Melanopsin (OPN4) is a retinal photopigment that mediates a wide range of non-image-forming (NIF) responses to light [1, 2] including circadian entrainment [3], sleep induction [4], the pupillary light response (PLR) [5], and negative masking of locomotor behavior (the acute suppression of activity in response to light) [6]. How these diverse NIF responses can all be mediated by a single photopigment has remained a mystery. We reasoned that the alternative splicing of melanopsin could provide the basis for functionally distinct photopigments arising from a single gene. The murine melanopsin gene is indeed alternatively spliced, producing two distinct isoforms, a short (OPN4S) and a long (OPN4L) isoform, which differ only in their C terminus tails [7]. Significantly, both isoforms form fully functional photopigments [7]. Here, we show that different isoforms of OPN4 mediate different behavioral responses to light. By using RNAi-mediated silencing of each isoform in vivo, we demonstrated that the short isoform (OPN4S) mediates light-induced pupillary constriction, the long isoform (OPN4L) regulates negative masking, and both isoforms contribute to phase-shifting circadian rhythms of locomotor behavior and light-mediated sleep induction. These findings demonstrate that splice variants of a single receptor gene can regulate strikingly different behaviors.